2017
DOI: 10.1016/j.cad.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Shape-optimization of 2D hydrofoils using an Isogeometric BEM solver

Abstract: In this paper, an optimization procedure, based on an Isogeometric BEM solver for the potential flow, is developed and used for the shape optimization of hydrofoils. The formulation of the exterior potential-flow problem reduces to a Boundary-Integral Equation (BIE) for the associated velocity potential exploiting the null-pressure jump Kutta condition at the trailing edge. The numerical solution of the BIE is performed by an Isogeometric Boundary-Element Method (BEM) combining a generic B-splines parametric m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 33 publications
(41 reference statements)
0
21
0
Order By: Relevance
“…Representative works of such studies can be found in Benzaken et al [Benzaken, Herrema, Hsu et al (2017)] and Herrema et al [Herrema, Wiese, Darling et al (2017)], where a surrogate model technique and a generalized pattern search algorithm, respectively, are adopted to optimize the wind turbine blades (see Fig. 6(c)) with complex geometries, Kostas et al [Kostas, Ginnis, Politis et al (2015)] where evolutionary algorithms are utilized to optimize ship-hull shape, Herath et al [Herath, Natarajan, Prusty et al (2015); Kostas, Ginnis, Politis et al (2017); Kostas, Fyrillas, Politis et al (2018)] with genetic algorithms, Lieu et al [Lieu, Lee, Lee et al (2018); Lieu and Lee (2019)] with an adaptive hybrid evolutionary firefly algorithm, Wang et al [Wang, Yu, Shao et al(2018)] with a chaotic particle swarm optimization method, and Zhang et al [Zhang, Li, Shen et al (2019)] with multi-island genetic algorithm and adaptive simulated annealing methods.…”
Section: Gradient-free Optimization Methodsmentioning
confidence: 99%
“…Representative works of such studies can be found in Benzaken et al [Benzaken, Herrema, Hsu et al (2017)] and Herrema et al [Herrema, Wiese, Darling et al (2017)], where a surrogate model technique and a generalized pattern search algorithm, respectively, are adopted to optimize the wind turbine blades (see Fig. 6(c)) with complex geometries, Kostas et al [Kostas, Ginnis, Politis et al (2015)] where evolutionary algorithms are utilized to optimize ship-hull shape, Herath et al [Herath, Natarajan, Prusty et al (2015); Kostas, Ginnis, Politis et al (2017); Kostas, Fyrillas, Politis et al (2018)] with genetic algorithms, Lieu et al [Lieu, Lee, Lee et al (2018); Lieu and Lee (2019)] with an adaptive hybrid evolutionary firefly algorithm, Wang et al [Wang, Yu, Shao et al(2018)] with a chaotic particle swarm optimization method, and Zhang et al [Zhang, Li, Shen et al (2019)] with multi-island genetic algorithm and adaptive simulated annealing methods.…”
Section: Gradient-free Optimization Methodsmentioning
confidence: 99%
“…When dealing with weakly singular integrals with singularities of the order ln(1/r) or 1/r such as those seen in equations ( 2)-( 4), ( 8), ( 9), ( 12)-( 13), (16), the transformation of variable technique proposed by Telles [28] is used. For equations (2) and (12), rigid body motion is also applied.…”
Section: Dbem For Plate Bending Problemsmentioning
confidence: 99%
“…One recent variation of the BEM is the isogeometric BEM [14,15,16]. The isogeometric BEM involves the use of Non-Uniform Rational B-Splines (NURBS) to represent the boundaries of the structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the effectiveness of the DBEM in fracture analysis, it has been extensively used in the research community mainly for problems involving 2D problems. Examples include topology optimisation [1], reliability analysis of structures subjected to fatigue [2], shape optimisation of hydrofoils [3], and the modelling of creep in concrete [4].…”
Section: Introductionmentioning
confidence: 99%